Positive relationship between Work-to-Sleep hours Ratio and obesity: a cross-sectional study, evidence from NHANES 2017–2023 - Zhou, Jinggang (Frontiers in Public Health, 2025)
BackgroundCurrent approaches relying solely on work hours or sleep hours often fall short in comprehensively assessing health risks. To address this gap, this study introduces a novel metric: the Work-to-Sleep hours Ratio (WSR). The study aims to investigate the relationship between WSR and obesity.ObjectiveTo investigate the correlation between WSR and obesity.MethodsWe employing data from 7,847 participants in the National Health and Nutrition Examination Survey (NHANES) 2017–2023. Data collected from all participants included demographic variables, health-related metrics and the presence of various health conditions. Logistic regression analysis, Restricted Cubic Spline (RCS) analysis, and interaction effects were employed to support the research objectives.ResultsIn the final model of multivariate analysis showed positive relationship between WSR and obesity (OR = 1.54, 95% CI:1.33–1.77, p < 0.001). Additionally, multivariate smooth splines analysis indicated that WSR exhibited a significant inverted L-shaped nonlinear relationship with obesity (P for nonlinearity < 0.05).ConclusionThe study observed a positive correlation between WSR and obesity, highlighting the importance of considering both work and sleep hours in assessing public health risks.